C4 constant vertebra: a novel benchmark of physiological cervical sagittal alignment - Xu, Haocheng; Gong, Zhaoyang; Yang, Yong; Zhang, Fan; Zou, Fei; Xia, Xinlei; Ma, Xiaosheng; Lyu, Feizhou; Jiang, Jianyuan; Wang, Hongli (European spine journal, 2024)
Background Cervical sagittal alignment is essential, and there is considerable debate as to what constitutes physiological sagittal alignment. The purpose of this study was to identify constant parameters for characterizing cervical sagittal alignment under physiological conditions. Methods A cross-sectional study was conducted in which asymptomatic subjects were recruited to undergo lateral cervical spine radiographs. Each subject was classified according to three authoritative cervical sagittal morphology classifications, followed by the evaluation of variations in radiological parameters across morphotypes. Moreover, the correlations among cervical sagittal parameters, age, and cervicothoracic junction parameters were also investigated. Results A total of 183 asymptomatic Chinese subjects were enrolled with a mean age of 48.4 years. Subjects with various cervical sagittal morphologies had comparable C4 endplate slope angles under all three different typing systems. Among patients of different ages, C2–C4 endplate slope angles remained constant. Regarding the cervicothoracic junction parameters, T1 slope and thoracic inlet angle affected cervical sagittal parameters, including cervical lordosis and C2–7 sagittal vertical axis, and were correlated with the endplate slope angles of C5 and below and did not affect the endplate slope angles of C4 and above. In general, the slope of the C4 inferior endplate ranges between 13° and 15° under different physiological conditions. Conclusions In the asymptomatic population, the C4 vertebral body maintains a constant slope angle under physiological conditions. The novel concept of C4 as a constant vertebra would provide a vital benchmark for diagnosing pathological sagittal alignment abnormalities and planning the surgical reconstruction of cervical lordosis.